2018
DOI: 10.3390/nu10111756
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence of the Antitumor, Antimetastatic and Antiangiogenic Activity of Ellagic Acid

Abstract: Ellagic acid (EA) is a naturally occurring polyphenolic compound endowed with strong antioxidant and anticancer properties that is present in high quantity in a variety of berries, pomegranates, and dried fruits. The antitumor activity of EA has been mostly attributed to direct antiproliferative and apoptotic effects. Moreover, EA can inhibit tumour cell migration, extra-cellular matrix invasion and angiogenesis, all processes that are crucial for tumour infiltrative behaviour and the metastatic process. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
135
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(153 citation statements)
references
References 118 publications
(113 reference statements)
9
135
0
1
Order By: Relevance
“…Ellagic acid is a polyphenolic compound reported to have antitumor, antimetastatic, and antiangiogenic properties . Studies have reported the presence of phytochemicals such as ellagic acid in SC and is implicated for its beneficial effect .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ellagic acid is a polyphenolic compound reported to have antitumor, antimetastatic, and antiangiogenic properties . Studies have reported the presence of phytochemicals such as ellagic acid in SC and is implicated for its beneficial effect .…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is involved in the action of several cancer‐chemotherapeutic agents. The selection of new drugs entity associated with apoptosis that would be expected to be effective against tumors and has been introduced into screening for new anticancer drugs . Apoptotic cells exhibit an early loss of phospholipid asymmetry and externalization of phosphatidylserine (PS) residues on the outer layer of the plasma membrane .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus here we tested EA on the Cryptosporidium infection model, we observed anticryptosporidial activity of this compound at micromolar concentrations (Fig 5A). The EA is a natural compound found in strawberries and other fruits, thus this compound have been used as dietary complement to treat several diseases 21,22 , interesting recently this compound showed its antimicrobial activity in the gastrointestinal pathogen Helicobacter pylori 23 . In order to investigate the mechanism of anticryptosporidial activity we evaluated expression proliferation (separine) and apoptosis markers (metacaspase) in the parasite.…”
Section: Discussionmentioning
confidence: 99%